Fuzzy Delphi Method identifies key training approaches in the parent-implemented intervention model for Autism - Ab Aziz, Analiza Anis; Mohamed Zain, Nor Azrita; Jusoh, Masnira; Zakaria, Rozanizam (e-IPH Ltd UK, 2025)
Early, family-centred support is crucial for children diagnosed with Autism Spectrum Disorder, as social communication and behaviour challenges could last forever. Although structured training is still scarce, the Parent-Implemented Interventions approach presents a promising means of empowering parents. This study applied the Fuzzy Delphi Method to get the expert agreement consensus on nine core training approach elements. Family Capacity-Building and Integrated Coaching are emerging as top priorities from all elements. These insights set the baseline for an evidence-based parent training model. Its long-term effects and adaptability to families with multicultural and multilingual backgrounds should be investigated in future studies